Respiratory muscle strength training for athletes: A narrative review - Subramanian, T.; Goyal, M. (Journal of Clinical & Diagnostic Research, 2025)
Respiratory Muscle Training (RMT) has become an alternative approach to boost athletic performance by improving respiratory function and delaying inspiratory muscle fatigue. The objective of the present study is to synthesise recent works on the benefits of RMT regarding muscle strength, respiratory system function and exercise performance in athletes and healthy individuals. The reviewed studies suggest that RMT can significantly increase pulmonary function parameters; however, the impact of RMT on these parameters remains inconsistent across studies. Regarding exercise performance, RMT has been shown to improve endurance, as evidenced by increased time to exhaustion, VO2 max, Repeated Sprint Ability (RSA) and postural control in some studies. This author aimed to analyse the different studies on respiratory training with the aforementioned outcomes. A thorough search of studies were conducted using various databases. The review included studies published in English, which were peer-reviewed and focused on RMT interventions in sports players. The following keywords were used as search strategies: RMT, Inspiratory Muscle Training (IMT), pulmonary function, Maximum Inspiratory Pressure (MIP), Maximum Expiratory Pressure (MEP), exercise performance, VO2 max and endurance training. All 10 studies were extracted based on their research design, including randomised controlled trials, pre-post experimental studies, randomised sham-controlled trials and randomised group factorial designs and were synthesised and analysed qualitatively. The activation of the metaboreflex mechanism and improved blood flow distribution to working muscles during exercise are proposed as potential underlying mechanisms for these performance benefits. However, the additive effects of RMT when combined with regular strength and endurance training remain debatable. The present analysis identified a suitable metric that could substantiate the evidence supporting the enhancement of athletic performance through RMT.